Meaningfulness of work and supervisory‐rated job performance: A moderated‐mediation model. Issue 6 (19th November 2020) - Fürstenberg, Nils; Alfes, Kerstin; Shantz, Amanda
Abstract: Meaningfulness of work has been heralded as one of the most important drivers of individual and organizational outcomes. However, the extent to which this critical psychological state manifests itself in the workplace and contributes to positive job performance is not yet fully understood. In this article, we draw from broaden‐and‐build theory to suggest that meaningfulness enhances employees' promotive voice behaviors, which in turn are positively related to job performance ratings by their leaders. We also suggest that leader–member relationships strengthen this mediational process. An analysis of survey data of 249 employees with matched lagged performance appraisal data supported our hypotheses. This study is important because it demonstrates that meaningfulness is not only associated with positive attitudinal responses and individual well‐being, but also holds value for organizations in that it fosters desirable workplace behaviors such as job performance.